Pengelolaan Dana Bergulir pada Lembaga Keuangan Mikro (LKM) Binaan Pmu Coremap II Wakatobi di Kecamatan Wangi-Wangi dan Wangi-Wangi Selatan - Mardin, Mardin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
The research objectives were to: (1) identify the actual problems of the revolving fund management held by the Program Management Unit (PMU) of Coral Reef Management Program phase II (COREMAP II) Wakatobi, (2) determine the solving recommendation according to the problems of the revolving fund management held by the PMU COREMAP II Wakatobi. The research was conducted from July through August 2011 in sub-District of Wangi-Wangi and South Wangi-Wangi, District of Wakatobi. The research populations were the personnel of the 24 village microfinance both Wangi-Wangi sub-District and South Wangi-Wangi sub-District. Descriptive statistic and cross-tabulation were used to reach the research objectives. Result of analysis indicated that the problems of the revolving fund management held by the PMU COREMAP II Wakatobi were: a) about 90,61% of the revolving fund was not running, b) the personal responsibility was lower, c) the lack of sanctions in the management system, d) the microfinance management system stay out of legal control of the village authority, e) the capacity of the personnel was lower, and f) misperception apart of the fund user toward the revolving fund allocation. Based on these actual problems, then the recommendation suggested were: a) the revolving fund must be managed by the available group or local institution (not be formed), b) It was necessary for the head of LKM to deliver a responsibility report at the time leader hand over, c) it was necessary to establish the sanction for each arrear in payments, d) the microfinance management must be controlled by the village legal authority, e) it was necessary to establish the qualification standard for the microfinance personnel, f) the continuity of technical assistance.